Development of a perceptually uniform physical scale for visual assessment of specular gloss. (25th January 2021) - Mohammadalizadeh, Ali; Mirjalili, Fereshteh; Ameri, Farhad; Moradian, Siamak; Ansari, Keivan; Safi, Mahdi
Abstract: Measuring gloss, visually or instrumentally, has been a challenge in many manufacturing and service industries. However, there exists no standardized method for visual evaluation of equidistance specular gloss. This study aimed to design and prepare a psychometric visually equispaced specular gloss scale for the visual measurement of gloss or any other geometric appearance attribute. To this end, a series of lithographically printed black papers, with different levels of gloss from low to high, were prepared to constitute a visually uniform specular gloss scale. Fourteen observers visually quantified the scale in a unidirectional illumination at three different geometries. Analyzing the results shows that the 60° geometry can quantify the equivalent specular gloss efficiently. A uniform specular gloss scale was prepared by assessing the prepared scale visually under the unidirectional illumination at the 60° geometry. Such a visually uniform specular gloss scale could be employed to develop a standard visual evaluation method of specular gloss in all related industries.